FRI0120 Prevalence and predictors of vertebral fractures after 5 years of disease activity steered treatment in patients with early active rheumatoid arthritis. (23rd January 2014) - Dirven, L.; van den Broek, M.; van Groenendael, J.H.; de Beus, W.M.; Kerstens, P.J.; Huizinga, T.W.; Allaart, C.F.; Lems, W.F.
Abstract : Background: Vertebral fractures (VFs) are more common in patients with rheumatoid arthritis (RA) compared to the general population. It is suggested that an appropriate control of disease, generally more effectively achieved with disease activity score (DAS)-steered treatment strategies, may prevent the development of vertebral fractures. Objectives: To determine the prevalence of VFs after 5 years of DAS-steered treatment in patients with early active RA and to investigate the association of VFs with disease activity, functional ability and bone mineral density (BMD) over time. Methods: Five-year radiographs of the lateral thoracic and lumbar spine of 275 patients in the BeSt study, a randomized trial comparing four treatment strategies, were available. Treatment adjustments were made every 3 months aiming at a DAS≤2.4. Vertebral fractures were assessed using the Genant method, with a fracture defined as loss of height reduction >20% in one vertebra. BMDs of the spine and hip were measured with dual energy X-ray absorptiometry. With linear mixed models, DAS and Health Assessment Questionnaire (HAQ) scores over 5 years were compared for patients with and without VFs. With GEE the association between BMD and VFs was determined. Results: At baseline patients were on average 54 years old and most were female (67%), of whom 18% were postmenopausal. Mean DAS was 4.4 and mean HAQ score was 1.3. After 5 years of DAS steered treatment, VFs were observed in 41/275 patients (15%). No difference in prevalence was found when stratified for gender, prednisone use and menopausal status. Disease activity over time was higher in patients with VFs, with a mean difference of 0.20 (95% CI:0.05-0.36). HAQ scores were higher in patients with VFs, independent of disease activity, with a mean difference of 0.12 (95% CI:0.02-0.2). Although values were slightly lower over time in patients with vertebral fractures, mean BMDs in the spine and hip over time were not independently associated with VFs (OR 0.99, 95%CI:0.78-1.25 and 0.94, 95%CI:0.65-1.36, respectively). Higher age was independently associated with VFs (OR 1.06, 95%CI:1.02-1.09). Conclusions: After 5 years of DAS-steered treatment, 15% of these RA patients had VFs. Higher age was associated with the presence of VFs, but mean BMDs in the hip and spine were not. VFs are associated with more disability, independent of disease activity. Patients with VFs have a higher disease activity over time, suggesting that VFs may be prevented by optimal disease activity suppression. Disclosure of Interest: None Declared